1970
DOI: 10.1002/1097-0142(197003)25:3<672::aid-cncr2820250324>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma in twins.Cutaneous malignant melanoma in identical twins from a set of triplets

Abstract: Identical twins and a fraternal triplet were studied because the identical twins developed malignant melanoma at age 53. Each had a preexisting mole, nearly identically placed on the left chest, which began to grow within 2 months of one another. The homozygosity of the twins was established with high probability by appearance, behavior, psychologic testing, deficiency of color vision, red cell typing, haptoglobin typing, dermatoglyphics, lymphocyte typing, mixed lymphocyte culture, lymphocyte transfer, and sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…St-Arneault et al . [7] described two identical male twins (from a set of triplets) who developed melanoma at age 53, at the same site and within a time frame of 2 months, while the fraternal triplet showed no evidence of tumour. More recently, Rao et al [8] reported two 71-year-old, identical female twins, diagnosed with melanoma at the same time (within 10 days of each other) and location (right calf).…”
Section: Discussionmentioning
confidence: 99%
“…St-Arneault et al . [7] described two identical male twins (from a set of triplets) who developed melanoma at age 53, at the same site and within a time frame of 2 months, while the fraternal triplet showed no evidence of tumour. More recently, Rao et al [8] reported two 71-year-old, identical female twins, diagnosed with melanoma at the same time (within 10 days of each other) and location (right calf).…”
Section: Discussionmentioning
confidence: 99%